Foreign experience of innovative activity of construction enterprises in developed countries - Lych, V.; Hazukin, A. (Ways to Improve Construction Efficiency, 2023)
This paper analyzes current trends in innovation in the construction industry of developed countries and identifies ways to adapt best practices to enhance the competitiveness of Ukrainian construction companies. Recognizing construction as a crucial sector of the economy, the authors note its significant negative impact on the environment due to waste generation, pollutant emissions, and ecosystem destruction. The study argues that innovative development is key to improving the environmental and economic efficiency of construction companies and ensuring sustainable development. Key factors shaping current trends in the construction industry abroad are identified, including the growing focus on sustainability and environmental responsibility, the ratification of international standards, changes in consumer preferences, the need for investment, high competition, and the digitalization of administration. The paper emphasizes the need to implement new technologies such as Building Information Modeling (BIM), automation, robotics, and 3D printing. The benefits of integrating green standards such as LEED, BREEAM, and Green Star, which contribute to reducing the negative environmental impact of the construction industry, are considered. Global trends, including environmental responsibility, digitalization, the use of energy-efficient and bio-based materials, and eco-conscious construction, are also analyzed. Based on the international experience of countries such as the United States, Germany, the United Kingdom, Japan, South Korea, and Australia, effective approaches to the innovative development of the construction industry are highlighted. Priorities for innovation in the United States include digitalization and the development of smart cities, while in European countries, the focus is on increasing environmental friendliness and energy efficiency, and in Japan, on robotics, automation, and earthquake-resistant technologies. The conclusion is that utilizing foreign experience in innovation in the construction sector will contribute not only to enhancing the competitiveness of Ukrainian construction companies but also to global environmental and economic sustainability.